Acquisition of bare nouns by Yoruba children - Arokoyá», Bá»lanle Elizabeth; Amaechi, Mary (Journal of Modern Languages, 2015)
This study is concerned with the acquisition of bare nouns by children acquiring Yoruba as their first language. The Minimalist Programme serves as the framework for our syntactic analysis of development of bare nouns by the Yoruba child. The database consists of longitudinal studies of a Yoruba child, Damilare, between the ages of fifteen (15) and thirty six (36) months. He was audio recorded daily by his mother within the period. Some of the data were also written directly. The results show that from a very early stage, the Yoruba child begins to acquire bare nouns as compared to other types of nouns and these nouns occur in different positions. It can be concluded that they use bare nouns where other types of nouns should be used but, with time, other nominal expressions are developed and are used appropriately.